Artificial Intelligence Impact on Responsabilities in Ethics Health Policy - AGHEORGHIESEI Doina-Monica; SFRIJAN Elena-Mihaela (Applied Research in Administrative Sciences)
The implementation of artificial intelligence (AI) in the healthcare sector brings both significant benefits and complex challenges related to ethical, administrative and legal responsibilities. To fully understand the impact of AI on health ethics policies, it is essential to analyze the recommendations of international organizations, national initiatives and recent academic studies. The integration of AI in healthcare is reshaping the responsibilities of professionals and decision-makers alike. In addition to its obvious benefits, AI raises critical concerns related to data privacy, diagnostic accuracy and liability in case of errors. This article examines how AI accountability and governance should be integrated into public health ethics policies, through an interdisciplinary approach that combines applied ethics, administrative sciences and policy analysis. We will argue that effective ethical governance of AI requires new institutional models, transparent policies and a clear distribution of responsibilities between human and technological actors.